2007
DOI: 10.1002/cne.21600
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and synaptic differences of the boutons of the projection neurons between the lip and collar regions of the mushroom bodies in the ant, Cataglyphis albicans

Abstract: The mushroom bodies of insects are viewed as key neuropils for sensory integration and perhaps learning and memory. In Hymenoptera, particularly ants, the calyx of the mushroom bodies is divided into two main regions, the lip and the collar. Although most ants are highly dependent on olfaction and have enlarged calyces comprised mostly of lip, some ant groups are also highly visual and have well-developed collars. The desert ant Cataglyphis albicans, known for its navigational abilities, shifts from the dark o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
(42 reference statements)
3
20
0
Order By: Relevance
“…10), suggesting a difference in the importance of boutons in the lip verses dendritic processes in the collar. Seid and Wehner (2008) provide evidence that synapse strength and efficacy (as measured by synaptic vesicles number and synapse size) differ between the lip and collar boutons in old workers and this study suggests that these differences in the coding of information may have a developmentally component.…”
Section: Role Of Glial Processes On Synapse Number and Axonal Pruningmentioning
confidence: 81%
See 1 more Smart Citation
“…10), suggesting a difference in the importance of boutons in the lip verses dendritic processes in the collar. Seid and Wehner (2008) provide evidence that synapse strength and efficacy (as measured by synaptic vesicles number and synapse size) differ between the lip and collar boutons in old workers and this study suggests that these differences in the coding of information may have a developmentally component.…”
Section: Role Of Glial Processes On Synapse Number and Axonal Pruningmentioning
confidence: 81%
“…It has been suggested that in older ants the difference in size of the boutons between the two regions is related to the differences in information integration between the lip and the collar (Seid and Wehner, 2008). Interestingly, bouton size and synaptic complexity does not differ in callows, which may indicate differences in processing visual verses olfactory information during development creates morphological dissimilarity in neuronal structures from a generic start.…”
Section: Axonal Bouton Size the Lip And The Collarmentioning
confidence: 93%
“…Comparison of the size of a microglomerular bouton with electron microscopy data confirmed a range of about 3 lm in diameter (Seid and Wehner, 2008) and assured that MG that fulfilled these criteria were exactly centered in an optical section with the distance between MG profiles closely resembling the density (Figs. 1 and 2).…”
Section: Laser Scanning Confocal Microscopy Image Processing and Damentioning
confidence: 90%
“…Each MG comprises a central presynaptic bouton of the projection neurons-originating from either the antennal lobes (AL) or the optic lobes (OL)-and a surrounding shell of numerous postsynaptic profiles, mostly from Kenyon-cell (KC) dendritic spines (Steiger, 1967;Ganeshina and Menzel, 2001;Gronenberg, 2001;Yasuyama et al, 2002;Frambach et al, 2004;Groh et al, 2004Groh et al, , 2006Seid and Wehner, 2008;Leiss et al, 2009). Previous studies have shown that both age and sensory experience can lead to volumetric changes in the MBs.…”
Section: Introductionmentioning
confidence: 99%
“…But they are in fact the rule in many entire nervous systems of invertebrates. This form of synaptic organisation is for example general in insects, triads being the most common in the Drosophila medulla (Takemura et al 2008) or mushroom body calyx of the ant Cataglyphis (Seid and Wehner 2008). Not only the brains of arthropods, but also nematodes (as in C. elegans: White et al 1986), and turbellarians (Reuter 1981) incorporate such synaptic modules, while those of molluscs such as Aplysia (Craig Bailey, personal communication) and ascidian larvae (Ryan and Meinertzhagen, unpublished data) do not.…”
Section: Structural Features Of Synaptic Contactsmentioning
confidence: 99%